2008
DOI: 10.1002/cd.209
|View full text |Cite
|
Sign up to set email alerts
|

Social class background and the school-to-work transition

Abstract: Whereas in years past, young people typically made a discrete transition from school to work, two ideal typical routes now characterize the sharing of school and work roles during adolescence and the transition to adulthood. Longitudinal data from the Youth Development Study show that one route involves less intensive employment during high school, followed by continued part-time employment and postsecondary educational investment. This pathway, more common for youth of higher-class origins, is especially bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 28 publications
1
61
1
Order By: Relevance
“…Staff and Mortimer (2008) stress the importance of studying effects of job quality, but existing studies are limited by small, non-representative, or older samples (Hansen and Jarvis 2000;Mortimer et al 2002;Entwisle et al 2005Entwisle et al , 2000Steinberg et al 1993).…”
Section: Previous Research On Adolescent Employmentmentioning
confidence: 99%
“…Staff and Mortimer (2008) stress the importance of studying effects of job quality, but existing studies are limited by small, non-representative, or older samples (Hansen and Jarvis 2000;Mortimer et al 2002;Entwisle et al 2005Entwisle et al , 2000Steinberg et al 1993).…”
Section: Previous Research On Adolescent Employmentmentioning
confidence: 99%
“…Arnett (2000: 478) notes that “social class may be more important than ethnicity, with young people in the middle class or above having more opportunities for the explorations of emerging adulthood than young people who are working class or below … [and poor youth may have] little chance for exploration of possible life directions.” Bynner (2005: 381) cautions that “assuming that most young people have the resources needed for navigation through the early stages of adult life may overlook the needs of those who have failed to gain the opportunity to embark.” Youth whose parents provide them with ample resources have more opportunities to prolong their education and delay their transition into full-time work (Staff and Mortimer 2008), and may have more opportunities to utilize role exploration as a way to find careers that best fit their talents and developing interests.…”
Section: Introductionmentioning
confidence: 99%
“…This finding gives a new dimension to earlier research that found that disadvantaged youth who work consistently have better educational outcomes, but no benefits accrued to youth who work only sporadically (Staff and Mortimer 2008). Consistent employment may have more benefits for young women than sporadic employment, such as by helping them develop adult skills, mature social networks, and self-efficacy to leave manipulative boyfriends.…”
Section: Discussionmentioning
confidence: 47%
“…Using data from the Youth Development Study, Staff and Mortimer (2008) found that disadvantaged youth who adopt the steady work schedules typical of middle-class youth — steady work less for than 20 hours per week, maintaining good grades — have higher educational attainment and better labor market outcomes. Conversely, advantaged youth who have the sporadic work schedules typical of disadvantaged youth (and youth with lower grades and educational aspirations) — many hours of work per week when employed with spells of non-employment — have lower levels of educational attainment and lower adult earnings (Staff and Mortimer 2008). They hypothesized that consistent work teaches adult time-management skills that prevent time-trade-offs.…”
Section: Introductionmentioning
confidence: 99%